Flavivirus enzyme-substrate interactions studied with chimeric proteinases: identification of an intragenic locus important for substrate recognition. - Preugschat, F (1991)
The proteins of flaviviruses are translated as a single long polyprotein which is co- and posttranslationally processed by both cellular and viral proteinases. We have studied the processing of flavivirus polyproteins in vitro by a viral proteinase located within protein NS3 that cleaves at least three sites within the nonstructural region of the polyprotein, acting primarily autocatalytically. Recombinant polyproteins in which part of the polyprotein is derived from yellow fever virus and part from dengue virus were used. We found that polyproteins containing the yellow fever virus cleavage sites were processed efficiently by the yellow fever virus enzyme, by the dengue virus enzyme, and by various chimeric enzymes. In contrast, dengue virus cleavage sites were cleaved inefficiently by the dengue virus enzyme and not at all by the yellow fever virus enzyme. Studies with chimeric proteinases and with site-directed mutants provided evidence for a direct interaction between the cleavage sites and the proposed substrate-binding pocket of the enzyme. We also found that the efficiency and order of processing could be altered by site-directed mutagenesis of the proposed substrate-binding pocket.